Treatment inequity in antiplatelet therapy for ischaemic heart disease in patients with advanced chronic kidney disease: releasing the evidence vacuum. (31st December 2023) - Varian, Frances L.; Parker, William A. E.; Fotheringham, James; Storey, Robert F.
Abstract: Chronic kidney disease (CKD) is a global health problem and an independent risk factor for cardiovascular morbidity and mortality. Despite evidence-based therapies significantly improving cardiovascular mortality outcomes in the general population and those with non-dialysis-dependent CKD, this risk reduction has not translated to patients with end-stage kidney disease (ESKD). Absent from all major antiplatelet trials, this has led to insufficient safety data for P2Y12 inhibitor prescriptions and treatment inequity in this subpopulation. This review article presents an overview of the progression of research in understanding antiplatelet therapy for ischaemic heart disease in patients with advanced CKD (defined as eGFR <30 mL/min/1.73 m 2 ). Beyond trial recruitment strategies, new approaches should focus on registry documentation by CKD stage, risk stratification with biomarkers associated with inflammation and haemorrhage and building a knowledge base on optimal duration of dual and single antiplatelet therapies. Plain Language Summary: What is the context? Patients with kidney disease are more likely to experience a heart attack than those without. Those with advanced kidney disease have a higher risk of death following a heart attack. Over the past two decades, advances in treatment following a heart attack have reduced the risk of death, however this has not translated to those with advanced kidney disease. Progression of kidney disease influences antiplatelet (e.g. clopidogrel) treatment efficacy. What is new? This contemporary review analyses registry and trial data to highlight some of the issues surrounding treatment inequity in patients with advanced kidney disease. This article describes potential mechanisms by which progression of kidney disease can influence clotting, bleeding and antiplatelet treatments. What is the impact? Further research into antiplatelet therapy for patients with advanced kidney disease is required. Registry and trial data can improve upon classification of kidney disease for future research. Future trials in antiplatelet therapy for advanced kidney disease are anticipated.